Investigating interdisciplinary collaboration : theory and practice across disciplines - Frickel, Scott, 1965-; Albert, Mathieu, 1959-; Prainsack, Barbara (American campus., 2016)
Universities in North America and Europe increasingly provide financial incentives to encourage collaboration between faculty in different disciplines, based on the premise that this yields more innovative and sophisticated research. Drawing from a wealth of empirical data, the contributors to Investigating Interdisciplinary Collaboration put that theory to the test. What they find reveals how interdisciplinarity is not living up to its potential, but also suggests how universities might foster more genuinely collaborative and productive research.